Edukasi Jelantah sebagai Sumber Energi pada Kelompok Ibu Rumah Tangga di Desa Petir, Bogor - Dyah Wulandani; Leopold Oscar Nelwan; Dwi Setyaningsih (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2021)
Jelantah is the used cooking oil. After being used more than three times for frying, the oil will be oxidized by ambient air, and dangerous free radical compounds are formed. Consuming of jelantah in certain amounts, can trigger diseases such as blockage of blood vessels, cancer and nervous disorders. In addition, jelantah discharged into the drains will cause blockage of drains and kill water ecosystems. However, jelantah can be used as an energy source and other products that have economic value. The purpose of this activity is to provide education for groups of housewives in Babakan Gang Salak, Petir Village, Bogor Regency regarding the dangers and benefits of jelantah, introducing simple technology of biodiesel production. The methods used include questionnaires, training and monitoring. The 1st, 2nd and 3rd trainings were held with different participants in the same location. The the participants’ enthusiasm and local site leaders was very high and they wished training for a wider range of participants. The training has been conducted successfully, which was showed that most of the participants could increase their skills and knowledge about the dangers and benefits of jelantah is biodiesel production. This knowledge is supposed to be applied in everyday life by not consuming jelantah for frying food, but it is used as a raw material for biodiesel production.